Генеративное развитие видов рода Pinus L., интродуцированных в Донецком ботаническом саду НАН Украины - Суслова, Е.П. (Промышленная ботаника, 2003)
The results of the ten-year studies of 26 Pinus L. species and forms, introduced in the Donetsk Botanical Gardens, Nat. Acad. Sci. of Ukraine are presented. The level of generative development of the species, the specific features of morphogenesis in generative buds, anomalous pollen grains, the viability of the pollen of the species under investigation were determined. It was noted that the high percentage of viable pollen is characteristic of the species originating from the Canadian, Central European, Eastern European provinces of the Circumboreal floristic region, province of the Atlantic Lowlands of the Atlantic-North American region, province of the Rocky Mountains of the Rocky Mountain region, and the Crimean-and-Novorossyisk province of the Mediterannean floristic region. The conclusion was made that 11 Pinus species have good prospects for their seed propagation in the south-east of Ukraine with view of their wide use in the urban greening and forestry.